Burnout in surgeons: A qualitative investigation into contributors and potential solutions. (May 2022) - Al-Ghunaim, Tmam; Johnson, Judith; Biyani, Chandra Shekhar; O'Connor, Daryl B.
Abstract: Background: Poor wellbeing affects the performance of all types of workers. Surgeons are particularly at risk of suffering from burnout, but minimal qualitative research has examined the causes of burnout and potential solutions in this group. Understanding this could inform the development of future burnout interventions. Purpose: This study aimed to explore the main factors that lead to surgeon burnout and to examine how surgeons cope with burnout at work. Setting: Surgical departments in the United Kingdom's National Health Service (NHS). Materials: Telephone interview and face-to-face interview. Methods: This qualitative study was conducted using semi-structured interviews with 14 surgeons from diverse specialisations. The interview consisted of two sections. The first addressed the main reasons for burnout. The second explored how surgeons manage burnout. Results: A thematic analysis identified several factors that can lead to surgeon burnout, captured in the themes of: rising to the challenge of surgical work; interpersonal conflict at work; greater demands than resources; the challenge of work-life balance; and the devastating impact of errors and poor patient outcomes. The study also revealed various strategies that surgeons employed to cope with burnout, namely: cognitive restructuring; seeking social support; stepping aside or down from the job; and prioritising personal health. Additionally, the study found some surgeons used maladaptive coping. Conclusion: Healthcare organisations, surgeons, and psychological experts should work together to provide more and improved interventions to help surgeons, which might lead to a reduction in the number of surgeons who leave the profession and help improve patient outcomes. Highlights: Burnout is driven by factors which are interpersonal or organisational in nature and amenable to interventions. Surgeons use a variety of tactics to deal with burnout, including both healthy and unhealthy habits such as substance misuse. Without a defined retention strategy, burnout causes some surgeons to step down from their jobs or emigrate.